A COMPARISON STUDY BETWEEN EPIC AND MODIFIED EPIC MODELS IN ASSESSING THE ERODIBILITY FOR ALLUVIAL SOILS - Safa Al-Qaisi; Khalid F. Hassan (Mesopotamia Journal of Agriculture)
The  study aimed to determine the effect of spatial variability on the  erodibility factor (K-factor) for alluvial  soils located at Tigris river bank using two empirical models ,KEPIC and modified KEPIC( Kr).The studied alluvial soils were extended along the adjacent area of Tigris river including three sites (Mosul Dam , Al-Rashidia and Al-Busaif).The results indicated that there is a wide variations between the two models in estimating the soil erodibility. It showed that use of the Kr model (modified KEPIC) would be considerably lead to under - estimation  prediction than KEPIC model. The lowest  values of  Kr model in comparison with KEPIC for three sites is related to that the Kr -model take into account the gravel fraction in their formula while the KEPIC is not. These finding indicate that the computing method of  soil erodibility  based on the Kr-model is reasonable and most suitable for estimation soil erodibility for  scientific and detailed studies of alluvial soils (as in our soil study) or in soils that have a considerable amounts of gravels separate in comparison to KEPIC  which can be used to determine the initial values of soil erodibility by water erosion.